2014
DOI: 10.1186/1471-2229-14-169
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analyses of multiple meristems of soybean: novel and alternative transcripts, evolutionary and functional implications

Abstract: BackgroundSoybean is one of the most important crops, providing large amounts of dietary proteins and edible oil, and is also an excellent model for studying evolution of duplicated genes. However, relative to the model plants Arabidopsis and rice, the present knowledge about soybean transcriptome is quite limited.ResultsIn this study, we employed RNA-seq to investigate transcriptomes of 11 soybean tissues, for genome-wide discovery of truly expressed genes, and novel and alternative transcripts, as well as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
193
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(195 citation statements)
references
References 90 publications
(133 reference statements)
2
193
0
Order By: Relevance
“…Recent studies have shown that more than half of these genes in rice undergo AS, either induced by stress conditions or developmentally regulated (E et al, 2013). However, detailed analyses of tissuespecific and developmental AS have so far been very limited (Wang et al, 2014) until our present study which provides new insights into AS of OsLpa1 in particular and gene AS in general in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that more than half of these genes in rice undergo AS, either induced by stress conditions or developmentally regulated (E et al, 2013). However, detailed analyses of tissuespecific and developmental AS have so far been very limited (Wang et al, 2014) until our present study which provides new insights into AS of OsLpa1 in particular and gene AS in general in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Because RNA-seq is not dependent on prior knowledge of gene sequences, the de novo assembly of transcripts in non-model plant species that lack a reference genome is possible . This approach has been widely used to characterize transcriptomes of non-model plants, such as soybean, rye (Secale cereale L.), tea (Camellia sinensis) and garlic (Allium sativum) (Haseneyer et al 2011, Shi et al 2011, Sun et al 2012, Wang et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The normalized expression values of the significantly differentially expressed mRNAs, lncRNAs, and miRNAs were extracted from the TCGA dataset and used for Euclidean distance-based hierarchical clustering analysis using the R package pheatmap (version 1.0.8, https://cran.r-project.org/package = pheatmap) [24]. The results of this analysis were displayed as a heatmap.…”
Section: Data Source and Preprocessingmentioning
confidence: 99%